Peran Media Platform Dimasa Pandemi Guna Menunjang Proses Belajar Mengajar Di SMA Harapan Nusantara Denpasar - Saputra, I Wayan; Sudarsana, I Ketut (Metta : Jurnal Ilmu Multidisiplin, 2023)
The education or teaching and learning process must still be carried out during a pandemic; this condition requires a strategy and the media platform's role to support the teaching and learning process, especially at Harapan Nusantara High School Denpasar. This study aims to reveal the part of the media platform during a pandemic to support the teaching and learning process at Harapan Nusantara High School Denpasar. This type of research is qualitative research. Data collection methods include literature studies, direct observation, and interviews. The collected data were then analyzed using data triangulation techniques: data reduction, data presentation, and data verification. Based on the findings in the study, it can be concluded: 1). The media platform's role during the pandemic was constructive and facilitated the process of teaching and learning activities both from the side of educators and students. 2) The advantage of the media platform is that it provides access to teaching and learning processes even during a pandemic; a pandemic is not an excuse not to study or not go to school. 3) The weakness of the media platform is monitoring the honesty of students in doing evaluations, following the process of teaching and learning activities cannot be controlled, and another weakness is the network which could be more stable.